How potential customers perceive companies' reply to negative reviews? - Tan, Wee-Kheng; Chen, Wei-Hung (The Service industries journal, 2024)
Companies are increasingly using humorous replies as a service recovery method to respond and apologize to complainants. However, there is a lack of clarity regarding the effectiveness and appropriateness of humorous replies. Drawing on information processing theory, this study assesses how consumers as onlookers view former customers' negative word-of-mouth relating to service failures (vindictive and nonvindictive reviews) and humorous and standard replies provided by service operators in the context of hostels, and effects on booking intentions. To compare consumers' responses to various combinations of reviews and replies, this study administered survey questionnaires to 377 respondents. A series of independent-sample t test analyses and partial least squares (PLS) path analyses revealed that standard replies are effective for responding to both review types. Humorous replies have better performance when responding to nonvindictive reviews than vindictive reviews. This study contributes to the scarce research on humorous replies in the service recovery context.